Fundamental rights at the crossroads of EU constitutionalism. Decoding the Member States’ key(s) to the Charter - Perez Fernandes, Sophie (Revista de Derecho Comunitario Europeo, 2018)
The internormative, comprehensive and constantly evolving system of fundamental rights protection progressively built within the European Union legal system and now coded in the Charter of Fundamental Rights of the European Union (CFREU) lies on a balance between the structure and the objectives of the European integration process and the protection of fundamental rights. After retracing some notable steps in order to demonstrate how the protection of fundamental rights has been sedimented at the heart of EU constitutional crossroads, the present text attempts to systematize the coordinates of the application of the CFREU to the Member States on the basis of the relevant ECJ case-law regarding art. 51(1) CFREU. The proposal will provide the frame of reference for the analysis of the Taricco saga as the most recent example of the intricate complexity of building the aforementioned delicate and crucial balance.